Catalytically active inclusion bodies as a potential tool for biotechnology - Bello, Muhammad Nura; Sabri, Suriana; Mohd Yahaya, Normi; Mohd Shariff, Fairolniza; Mohamad Ali, Mohd Shukuri (John Wiley and Sons, 2024)
The initial assumption that viewed inclusion bodies as a hindrance to the efficient production of protein is no longer held due to the emergence of catalytically active inclusion bodies (CatIBs). Recent studies revealed their potential to be used in free form or immobilized as biocatalysts. The curiosity to acquire suitable catalysts has remained the measure of concern for researchers and industrialists. Numerous processes and production in various sectors of food industries, petroleum, pharmaceutical, cosmetics, and many others are still searching for a robust catalyst with outstanding features such as recyclability, resistance to pH, as well as temperature. CatIBs are forms of inclusion bodies that possess catalytic activity, which can improve catalysis efficiency, stability, and recyclability. One of the advantages of CatIBs is their potential to be used as catalysts for numerous bioprocesses when generated by an enzyme. These aggregates can efficiently be used as a replacement for traditional enzyme immobilization. This review tends to focus on the possibility of its application in various processes. The novelty of this review is that it considered the production of CatIBs both from artificial and natural perspectives, as well as how to improve it. Inclusion bodies’ immobilization may provide an efficient alternative in the area of biocatalysis, and hence it will improve industrial sectors and substantially provide a means of achieving excellent performance in the near future.